Assigning metadata to digital books in EPUB3. Part one: metadata in EPUB3 specifications - Centelles Velilla, Miquel (BiD: Textos Universitaris de Biblioteconomia i Documentació, 2015)
Objectives: This paper describes how to use internal and descriptive metadata in EPUB 3 according to current standards and the good practices disseminated by the publishing industry. It also offers a series of recommendations which will be especially useful for small publishers and book authors wishing to publish their own works. -- Methodology: The paper is descriptive and instructive, using an explanation of the internal structure of a book in EPUB3 format to consider different metadata elements and corresponding standards, their structure and possible values. The authors use a case study to exemplify their recommendations. -- Results: The EPUB mechanisms that describe the context, content and structure of books essentially emulate the tools that are specifically designed for cataloguing, an indication of the consolidation of the metadata model in its origin. The authors especially recommend the inclusion of five mandatory metadata elements: identifier, title and language, as drawn from the Dublin Core standard, and two further elements, selected according to the user’s own scheme, to describe the date of the last modification and the duration of the audiovisual media included.